Learning Management by Widyaiswara on Supervisor Leadership Training - Apriani, Tasia; Saepudin, Asep; Saripah, Iip (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This study aims to determine the management of Widyaiswara learning in the IX Leadership Training and Education class in 2021 at the PPSDM of the Ministry of Home Affairs Regional Bandung. The method used in this research is descriptive with a qualitative approach. Data was collected by direct observation, interviews and documentation studies. Testing the validity of the data is done by triangulation of sources, while the data analysis uses the techniques of reduction, display, and drawing conclusions. The results showed that 1) The planning that had been prepared by the widyaiswara was that the widyaiswara's motivation was optimal in collecting GBPP/SAP and teaching materials. 2) The implementation of learning uses an adult approach with lecture, discussion, role play, and brainstorming methods. Communication aids used such as loudspeakers and infocus, the learning process is carried out in the classroom and also outside the classroom (field learning practice). Motivation is done by making a commitment to study, ice breaking, and coffee breaks. 3) Learning evaluation is carried out through the provision of material assignments, discussions, and assessment of field learning outcomes, both in the form of pre-test and post-test.